Developing the prediction model for mitigating the abandoned housing projects in malaysia - Saidah An’nisaa, Salam (2023)
Abandoned housing projects is a relentless global issue which carries no positive value to involving stakeholders, economy, and sustainable aspects as well. Abandoned housing projects in Malaysia had prevailed since 1970 and the numbers are heavily escalating regardless of the Malaysian government’s efforts to curb the issue through promulgation of numerous incentives, policies, and laws. The incompletion of housing project could detriment the surrounding environment and social aspect as well as negatively impact the economy at a national scale. Nonetheless, homebuyers are the direct victim of this matter following the un-fulfillment of their intention to own a property in addition to extension of commitment for rental arrangement. To certain extent, unfortunate homebuyers would become ineligible for international travel and loan application from financial institutions ensuing failed housing loan payment. Therefore, the aim of the study is to analyze the factors that contribute to the abandonment of housing projects and its impact towards the nation, environment, and society. Through semi-structured interview session with 10 expert panels with the information generate from extensive literature review from previous study, several factors and impacts had been listed. A quantitative research methodology was conducted for data collection through a well-designed questionnaire which was developed based on the extensive literature review, semi-structured interviews, and discussions with expert panels. The 100 respondents in this study incorporated population of housing development stakeholders such as developers, contractors, consultants, and local authorities. Data collected was analyzed using the descriptive statistics of Ordinal Logistic Regression (OLR) method to satisfy second objective of the study whereby the relationship between each factors that contributes to the abandoned housing project and the project status was obtained. Subsequently, the probability for 3 category of project status was also developed to illustrate the probability of project status. The third objective of this study determines the solution priorities to mitigate the abandoned housing project through a pair wise questionnaire survey. This study utilizes Analytical Hierarchy Process (AHP) to derive the weighted value for each criterion by comparing the criteria with several alternatives to which the highest value would indicates the best solution to mitigate the abandoned housing project. The last objective is developing the prediction model to mitigating the abandoned housing project by combining the result gathered from objective two and objective three. Finally, by combining the finding from objective 2 and 3 the prediction model to mitigate the abandoned housing project developed. The findings conclude that the main factors of abandoned housing project are financial factors, followed by project participant factors, project management factors, market signal, procurement factors, and lastly, external factors. During the project monitoring process, the AHPM can displayed capability in predicting project status with regards to the issues (factors of abandoned housing project) faced in each project. In addition, most of the respondents stressed that developers facing financial difficulties should prepare alternative fund in order to settle their financial problems, such as by utilizing the developer community cooperation fund. The respondents agreed that the issue could be rectified through proper planning during preliminary study, proper scheduling during the construction phase, incorporating public private partnership (PPP), joint venture, and adequate study on the market signal. These findings could assist the stakeholders involved in mitigating the problems of abandoned housing projects in Malaysia.